Towards a theoretical framework for understanding Muslim-centered user interface design - Nasaruddin, Zan Azma; Hussin, Husnayati (2013)
User interface is a discipline which focuses on the principles of design and metaphor in the digital landscape. However, normally the development of user interface is standardized in order to cater compatibility. Some evidence indicate that the application of standardized solution pose problems to some ethnic groups. Hence, some researchers suggested that interface design should consider the cultural aspects. Although localization is adopted in some web designs, more insights is needed on culture-centered design. This study focuses on understanding the Islamic culture and interface design. As Muslims form a large proportion of the world population, and the percentage of Internet users among them is rising, it is imperative that a more suitable approach in interface design is explored. A framework of Muslim Centered User interface Design (MCUID) is proposed inspired from Culture- Centered Design. Several relevant theories are explored and used as a basis in the construction of the framework.